José Benito de Churriguera en Salamanca (1692-1699) - Rupérez Almajano, María Nieves (Anuario del Departamento de Historia y Teoría del Arte, 1998)
This article is based on the work developed by José de Churriguera in Salamanca, nearly completely unknown till a few years ago. We have been able to determine exactly the time of his coming back to Madrid, in April 1699, through papers and fix with more details some of the works he was busy in this town. You can see features that allow us to connect him with the tradition from Madrid in which he had been educated. Apart from the works at St. Stephs's in Salamanca, well known, we have worked on the school of Oviedo chapel analysing its building process, begun in 1694 and its most characteristic features. We have identified our Lady of Sorrow's chapel whose authorship is given to him, and we have done a detailed study of it. Besides, we said what his work was in the St. Agustin's Convent and the reasons of his lawsuit that lasted until he died. Finally, we mention to other less important works in which he took part as the building of the "camarin" of St. Benito's church, an altarpiece in Carbajosa or different expert reports.